Hypercontent Media for Fostering Sociopreneurship in Vocational Education: Media Hiperkonten untuk Menumbuhkan Sociopreneurship dalam Pendidikan Vokasi - Safitri, Erna Retna; Raharjo, Makmum; Saputra, Ardi; Suningsih, Taruni; Trayati, Erni (Universitas Muhammadiyah Sidoarjo, 2024)
This research explores the synergy between sustainable environmental education, sociopreneurship, and hypercontent media to support the SDGs and enhance 21st-century education. Focusing on vocational school students, it aims to design hypercontent-based learning media to promote sociopreneurship. The study uses qualitative methods with a case study approach, involving leaders, teachers, and students from five Vocational High Schools in Palembang. Data were collected through literature and field studies, including a media needs analysis via a questionnaire. The results indicate good school readiness for sustainable education programs, with an average score of 4.06. However, classroom implementation is low at 62.25%. Only 34% of students find current media effective, while 65% feel that traditional methods are insufficient. Therefore, 80% of students see the need for hypercontent-based learning media. Keywords: Sustainable Environmental Education, Hypercontent, Sociopreneurship, Sustainable Development Goals, Instructional Media